The Correlation between the Emergency (Triage) and Anxiety Levels of Nurses in the Emergency Room at Royal Prima General Hospital Medan - Adhayani Lubis; Bagus Raharja; Muhammad Andriady Saidi Nasution (Postgraduate, University of Mataram, 2023)
Urgent and emergency can be stated to be a situation of body health that requires immediate medical treatment to save life. The Emergency Room is a very important entry point for healthcare services for the patients who need urgent treatment and care. both urgently and emergency. Patients who enter the ER in emergency conditions will be triaged and it aims to classify the patient's emergency condition. This condition can cause anxiety experienced by nurses when they are in the ER. This research aims to determine the correlation between the emergency (Triage) and anxiety levels of nurses in the Emergency Room of Royal Prima General Hospital Medan. This type of research used an analytical design association with a cross sectional approach. The sample in this study involved thirty-seven nurses. Data analysis used univariate and bivariate analysis. The results of the study revealed that the majority of nurses handled patients with a red emergency (triage) level of 19 (5.40%). The majority of nurses handled patients with a red emergency (triage) level of 19 (51.40%). The majority of nurses experienced a level of anxiety in the emergency room at Royal Prima General Hospital Medan with thirteen (35.10%) nurses in the very severe anxiety category. There is a correlation between the emergency (Triage) and anxiety levels of nurses in the Emergency Room at Royal Prima General Hospital Medan with the p-value is < 0.05.